Single Channel Instrument for Simultaneous Rotation Speed and Vibration Measurement Based on Self-Mixing Speckle Interference - Xiulin Wang (IEEE, 2022)
In this paper, a novel method for simultaneous measurement of rotation speed and vibration based on self-mixing speckle interference (SMSI) has been demonstrated. In view of the autocorrelation characteristic of SMSI, the time delay of laser incident during one rotation period is determined, and the rotation speed of the object is calculated according to the mathematical relationship. At the same time, the signal square-wave conversion and the global maximum fringe-counting method are proposed to measure the vibration displacement subject to the rotation. The theory and signal processing means are introduced in detail, and a series of experiments employing computer disk at different positions with various rotation speeds indicate that the proposed method achieves a simple, efficient, and accurate multi-parameter measurement.